RANCANGAN TERMOELEKTRIK GENERATOR (TEG) PORTABEL PADA KNALPOT SEPEDA MOTOR DENGAN MATERIAL ALUMUNIUM SEBAGAI KONDUKTOR - Hudaya, Chairul (Jurnal TAMBORA, 2021)
Thermoelectric Generator (TEG) is an application of the thermoelectric module forgenerate electricity according to the seebeck effect which takes advantage of the temperature differenceoccurring on both sides of the module. This study aims to design a toolportable power generator by exploiting the energy loss in motorcycle exhaustin order to produce a power of 10. The design that is built is in the form ofelectrical design with series configuration and series-parallel configuration ascomparison, using 8 pieces of thermoelectric modules of type SP1848-27145 and modulesDC / DC converter. The mechanical design consists of 4 layers with visualizationusing Autodesk Inventor software. The shape of the tool is adapted to the shapeexhaust so that it can be removed and reinstalled with dimensions of 164.3 ????????× 205 × 23.135 ???????? and can maintain the temperature difference (????????) of 60 ° ????. ResultThe selected design uses a series configuration because it has the same amount of powerclose to the target of ? 9???? with good reliability and has protection onconverter step-down module.